Predictors of online and offline activism in hybrid regime society – Serbian study. - Pedović, Ivana; Pejičić, Marija; Đorić, Stefan (British Journal of Psychology, 2025)
In Serbia, categorized as a hybrid or semi‐authoritarian system by Freedom House, exploring activism is crucial. Two cross‐sectional studies were conducted to examine predictors of online and offline civic activism in a society favouring punitive measures and limiting open dialogue. The first study involved 1107 participants (65.1% female, 33.2% male and 1.6% in other categories; Mage = 28.15 years), while the second included 2306 individuals (67.5% female, 30.2% male and 2.3% in other categories; Mage = 28.1 years). We modelled the relationship between predictor variables and a dependent variable at different quantiles of the distribution (25th, 50th, 75th and quantile marked with theoretical middle points of online and activism scales) using quantile regression. Results highlighted perceived policy control, social generativity and conscientiousness as key predictors across different levels of both online and offline activism. Personality traits like extroversion, neuroticism and honesty have different effects on online versus offline activism, suggesting different motivations. Additionally, future‐oriented people participate more offline. The quantile regression, analysing coefficients at different points in the distribution, offered valuable insights into manifestations of activism. These findings are discussed highlighting the complex dynamic of different factors in shaping civic engagement in Serbia's challenging sociopolitical landscape.